Cytoskeleton-disrupting agent cytochalasin B reduces oxidative stress caused by high glucose in the human arterial smooth muscle - Kazumi Takaishi; Hiroyuki Kinoshita; Guo-Gang Feng; Toshiharu Azma; Shinji Kawahito; Hiroshi Kitahata (Elsevier, 2020)
The role of cytoskeleton dynamics in the oxidative stress toward human vasculature has been unclear. The current study examined whether the cytoskeleton-disrupting agent cytochalasin B reduces oxidative stress caused by high glucose in the human arterial smooth muscle. All experiments in the human omental arteries without endothelium or the cultured human coronary artery smooth muscle cells were performed in d-glucose (5.5 mmol/L). The exposure toward d-glucose (20 mmol/L) for 60 min reduced the relaxation or hyperpolarization to an ATP sensitive K+ channel (KATP) opener levcromakalim (10−8 to 3 × 10−6 mol/L and 3 × 10−6 mol/L, respectively). Cytochalasin B and a superoxide inhibitor Tiron, restored them similarly. Cytochalasin B reduced the NADPH oxidase activity, leading to a decrease in superoxide levels of the arteries treated with high d-glucose. Also, cytochalasin B impaired the F-actin constitution and the membrane translocation of an NADPH oxidase subunit p47phox in artery smooth muscle cells treated with high d-glucose. A clinical concentration of cytochalasin B prevented human vascular smooth muscle malfunction via the oxidative stress caused by high glucose. Regulation of the cytoskeleton may be essential to keep the normal vascular function in patients with hyperglycemia.